Localized Subcutaneous Insulin-Derived Amyloidosis Excised after Evaluation Using Ultrasonography in a Patient with Type 2 Diabetes Mellitus - Seiya Hagiwara; Shinji Taneda; Takaya Fukumoto; Kazuya Hagiwara; Minoru Kikuchi; Tetsunori Kimura; Hidetaka Nakayama; Naoki Manda (Case Reports in Endocrinology)
A 62-year-old man with type 2 diabetes mellitus, who had been on insulin therapy for the past 20 years, was found to have subcutaneous mass formation in the abdomen during a workup of worsened glycemic control. Because of suspected amyloid deposition, he was advised to avoid injections to the mass, which led to improvement of glycemic control. However, he strongly requested mass excision and was hospitalized. After evaluation using ultrasonography and computed tomography, a total mass excision was performed, and a diagnosis of insulin-derived amyloidosis was made. Comparison of the ultrasonographic and histopathological findings demonstrated that the location of the amyloid deposition nearly corresponded to the hypoechoic region. This case highlights that ultrasonography, which is a noninvasive imaging modality, can be useful for detection of insulin-derived amyloidosis.